Making a Nuisance of Takings Law - Robert L. Glicksman (Washington University Journal of Law & Policy, 2000)
The purpose of this Essay is two-fold. First, by assessing how lower federal courts and state courts have interpreted and applied the nuisance exception to takings liability staked out in Lucas, it bears out Professor Mandelker’s 1993 prognostication that commentators would subsequently explore the parameters of that exception. Second, by analyzing the post-Lucas decisions, it assesses whether Lucas’s treatment of the nuisance exception has turned out to be the radical and destructive break with tradition that Mandelker feared.
Keywords: Land use; Nuisance; Regulatory taking (Law)